PENGARUH DISIPLIN KERJA DAN LINGKUNGAN SEKOLAH TERHADAP KINERJA GURU DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA SMAN 1 TAEBENU KABUPATEN KUPANG - Tarigan, Rosmeri Br; H. Kaluge, Agapitus; Sia Niha, Simon; Talok, Damianus; A. Manafe, Henny (ITB AAS Indonesia Surakarta, 2024)
Abstract The type of research used in this study is structural in nature, namely looking for the relationship between discipline and the school environment on the performance of Taebenu 1 Public High School teachers with motivation as the mediating variable. the sample used in this study were 53 teachers. Data were collected by interview, questionnaire and documentation techniques and analyzed using descriptive and inferential statistics using the Smart PLS 3.8 application. The results of the descriptive statistical analysis show that the variable teacher performance is 77.74%, work discipline is 79.15, school environment is 78.36% and work motivation is 80.05% which is included in the good category. Inferential statistical test results show that 1) the work discipline variable has no significant effect on the performance of Taebenu 1 Public High School teachers with a tcount of 0.006 and a significant value of 0.995. 2) the work discipline variable has a significant effect on the teacher's motivation at SMAN 1 Taebenu with a tcount of 3.918 and a significant value of 0.000. 3) school environment variables have a significant effect on teacher performance at SMAN 1 Taebenu with a tcount of 2.632 and a significant value of 0.009. 4) school environment variables have a significant effect on teacher motivation at SMAN 1 Taebenu with a tcount of 2.205 and a significant value of 0.028. 5) the variable of work motivation has a significant effect on teacher performance at SMAN 1 Taebenu with a tcount of 2.982 and a significant value of 0.003. 6) that the work discipline variable has a significant effect on teacher performance at SMAN 1 Taebenu through the work motivation variable with a tcount of 2.171 and a significant value of 0.030. Direct testing shows that work discipline has 9no significant effect on teacher performance. 7) school environment variables have no significant effect on teacher performance at SMAN 1 Taebenu through work motivation variables with a tcount of 1.710 and a significant value of 0.088. Direct testing shows that the school environment has a significant effect on teacher performance. The coefficient of determination shows that the ability of the work discipline and school environment variables to explain the mediating variable is 40.5% and the remaining 59.5% is contributed by other variables not included in this research model. Furthermore, the ability of work discipline, school environment and work motivation variables in explaining teacher performance variables is 47.7% and the remaining 52.3% is the contribution of other variables not included in this research model. Based on the results of this study, it can be suggested to SMAN 1 Taebenu to improve teacher performance by considering the variables of work discipline, school environment, and work motivation. . Keywords : Teacher Performance, Work Discipline, School Environment, and Work Motivation